Insights into the horizontal movements, migration patterns, and stock affiliation of California swordfish. (11th January 2020) - Sepulveda, Chugey A.; Wang, Michael; Aalbers, Scott A.; Alvarado-Bremer, Jaime R.
Abstract: This study reports on the horizontal movements of swordfish ( Xiphias gladius L.) tagged during deep‐set fishery trials off the California coastline. Position estimates from several electronic tag types were used to better understand swordfish stock structure and regional affiliation with current boundary hypotheses used to manage swordfish in the eastern north Pacific. Swordfish were outfitted with (a) satellite‐linked mark–recapture tags ( n = 66), (b) electronic data storage tags that were recaptured ( n = 16), (c) fin‐mounted Argos transmitters ( n = 6), and (d) satellite‐linked archival tags ( n = 4). Twenty‐six percent of tagged swordfish reported close to (<225 km) their deployment location within the southern California Bight (SCB). Of the 50 swordfish that moved outside the SCB, 76% exhibited affiliation to the Eastern Pacific Ocean (EPO) management unit, 20% moved into the Western and Central North Pacific (WCNP) and 4% spent time within both the EPO and WCNP boundaries. Mean displacement between deployment and reporting locations was 1, 250 ± 1, 375 km, with daily rates of movement up to 55 km/day. Seasonal migrations ranged from the equator (0.8°N.132.4°W) to the Hawaiian Islands (17.0°N/154.2°W), with multiple individuals returning to the initial tagging locations the subsequent season. Seasonal site fidelity exhibited by several individuals highlights the importance of the SCB foraging grounds. While no evidence of trans‐equatorial or trans‐Pacific crossing was documented, extensive movements validate the highly migratory nature of California swordfish and support the need for future inclusion of spatial distribution data in management. Findings suggest that SCB swordfish may exhibit a higher level of EPO connectivity than previously proposed.